Correlates of Perceptions, Use, and Intention to Use Heated Tobacco Products Among US Young Adults in 2020. Issue 12 (28th July 2022) - Duan, Zongshuan; Wysota, Christina N; Romm, Katelyn F; Levine, Hagai; Bar-Zeev, Yael; Choi, Kelvin; Berg, Carla J
Abstract: Introduction: Despite the increased heated tobacco product (HTP) marketing in the United States, little is known about HTP perceptions and correlates of HTP use and use intentions among young adults. Aims and Methods: Using 2020 cross-sectional data from 2, 470 young adults (ages 18–34) from 6 US metropolitan areas, we conducted exploratory factor analysis to identify factors regarding perceived utility/appeal of HTPs, specifically IQOS, and examined these factors in relation to lifetime HTP use and use intentions, using multivariable logistic and linear regression, respectively. Results: 19.1% had heard of HTPs and 4.1% ever used HTPs; 14.7% had heard of IQOS specifically and 2.8% were ever-users. Use intentions were low ( M = 1.27, scale: 1 = not at all to 7 = extremely). Factor analysis identified five perceived utility/appeal factors: innovation ( M = 3.17, scale: 1 = not at all to 7 = extremely), cigarette substitute ( M = 2.99), and youth appeal ( M = 2.82), e-cigarette/nicotine substitute ( M = 2.36), and fashionable ( M = 2.04). Controlling for sociodemographics and other tobacco use, perceiving IQOS as more fashionable and e-cigarette substitutes positively correlated with lifetime HTP use (aOR = 1.60, 95%CI = 1.17, 2.17; aOR = 1.48, 95%CI = 1.11, 1.97, respectively) and use intentions (β = 0.26, 95%CI = 0.21, 0.30; β = 0.14, 95%CI = 0.09, 0.18); perceiving IQOS as cigarette substitutes negatively correlated with ever use (aOR = 0.74, 95%CI = 0.56, 0.97) and use intentions (β = −0.06, 95%CI = −0.10, −0.03). Correlation patterns were similar among past-month cigarette, e-cigarette, and any-tobacco users. Conclusions: Although HTP awareness and use were low, monitoring HTP perceptions and reasons for use as HTPs become more prominent is critical in anticipating their potential impact, particularly as more products seek FDA authorization to use reduced risk or exposure marketing claims. Implications: Awareness, ever use, and intentions to use heated tobacco products (HTPs) were low among US young adults in 2020. Perceiving IQOS as fashionable and an e-cigarette substitute were positively correlated with ever use and intention to use HTPs. In addition, perceiving IQOS as a cigarette substitute was negatively correlated with ever use of HTPs and HTP use intentions. Continued surveillance on perceptions and use behaviors is needed to better understand use patterns, intentions to use, and reasons for using HTPs.